Gestión de talento humano y su incidencia en el rendimiento financiero de la Empresa Álvarez - Albán Álvarez, Walter William (2020)
The present investigation entitled: Human Talent Management and its Incidence in the Financial Performance of the Álvarez Company is developed, in order to study the problems that the distributor represents, for this, a documentary investigation is carried out, where concepts of authors are taken national and international on human talent management and financial performance. Through surveys directed to the clients of the Álvarez distributor, I know evidence that there are problems within the company. These evidenced results allowed to shape a proposal that adapts to the reality of the distributor, improving what has been considered convenient for the continuity of the company.